Детская книга - Акунин Борис (Романы Б. Акунина, 2007)
Экземпляры: Селтинская районная библиотека (аб) (20191008) / Инвентарный номер: 192194 / Цена: / Авт.знак: А 44 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6